Occurrence of Defects in Laser Beam Welded Al-Cu-Li Sheets with T-Joint Configuration - Higashi,André Luiz de Carvalho (2012)
Abstract: In the aerospace industry, laser beam welding has been considered as one of the most promising routes among the new manufacturing processes. Substitution of riveting by laser beam welding of aircraft structures has contributed to weight and cost savings. Concurrently, new aluminum alloys have been developed with the addition of lithium with better mechanical properties and lower density. The Al-3.5%Cu-1.1%Li alloy (AA2198) is one of these new generation alloys. However, laser beam welding of Al-alloys expectations might be greatly reduced by the occurrence of two main defects: porosity and hot cracking. Porosity is mainly caused by the entrapment of lithium gases, followed by rapid solidification. On the other hand, hot cracking happens due to the conjunction of tensile stresses, which are transmitted to the mushy zone by the coherent solid underneath, and to an insufficient liquid feeding to compensatefor the volumetric changes. This work intended to contribute towards the knowledge of AA2198 'welding metallurgy, utilizing a 2-kW-ytterbium-dopedfiber laser. The T-joint configuration welds were performed autogenously or with the addition of an AA4047 filler ribbon. Ali the weld beads presented high porosity level, but with a decreasing tendency when welding from both sides. The use of the filler material could solve hot cracking problem. The best results are observed using two runs (both sides) with filler and a speed of 2 m/min and power of 1,200 W. The T-pull tensile strength obtained under these conditions was 178 MPa, which is below the tensile strength of the unwelded AA2198 sheet but higher than the AA6013 welded in similar conditions.